Strength-Based Therapy: Empowering Athletes' Self-Efficacy and Life Satisfaction - Parsakia, Kamdin; Knechtle, Beat; Irandoust, Khadijeh (Health Nexus, 2024)
While it is known that focusing on positive attributes and capabilities can enhance psychological resilience, the specific effectiveness of strength-based therapy in improving self-efficacy and life satisfaction among athletes remains unexplored. By emphasizing positive attributes and capabilities, strength-based therapy aims to enhance athletes' psychological resilience and overall well-being, which are crucial in the highly competitive and physically demanding world of sports. Therefore, this study investigates the effectiveness of strength-based therapy in enhancing the self-efficacy and life satisfaction of athletes. The study used a quasi-experimental design with 50 competitive athletes aged 18-35. The methodology included an 8-week intervention focusing on leveraging individual strengths, goal setting, and resilience building. Outcomes were measured using the General Self-Efficacy Scale and the Satisfaction with Life Scale. To examine these differences, an analysis of variance with repeated measures, coupled with Bonferroni’s post-hoc test, was conducted using SPSS-26. Results indicated significant improvements in both self-efficacy and life satisfaction in the experimental group compared to the control group. The study concludes that strength-based therapy positively impacts athletes' psychological well-being, suggesting its potential for broader application in sports therapy.